Pengembangan Pembelajaran Digita Era 4.0: Media Animasi Pahlawan Sisingamangaraja XII - Apriani Harahap; Deny Setiawan; Rosnah Siregar (Universitas Negeri Medan, 2020)
This article aims to develop the animation media of hero Sisingamangaraja XII which is digitally packaged in the 4.0 era of students so that they can enhance the national character of national heroes in their regions. The location of the study was conducted in the first semester students of the basics of developing social studies material at the Faculty of Social Sciences, Medan State University. Research refers to Borg & Gall's research and development research theories and models. The development model is summarized into three stages of activities namely (1) a preliminary study, namely: observation and study of literature. (2) Development is carried out by making scripts, storyboards and making video animations. (3) The evaluation phase consists of evaluating the media and material experts and evaluating small groups. This media deserves to be utilized with the results of the validation of 85% of instructional media experts and product trials. This shows that this animation media is very populated as learning media of the digital era 4.0, especially learning materials, Fundamentals of Social Sciences material.